A Study on Characterization of the Main Character in “The Fault in Our Stars” - Annisa Patmarinanta; Potjut Ernawati (Universitas Syiah Kuala, 2016)
This research analyzes The Fault in Our Stars, a novel by Green (2012). The Fault in Our Stars is one of Green’s novels that reflect the reality of life. This research focuses on the personalities of Hazel and August, the main characters of the novel. The author took from (Djasi, 2000) as the framework of the main character characterization. The design of this study was a descriptive qualitative study. The aim of this study is to see Hazel’s and August’s personalities as the main character of The Fault in Our Stars. By examining the character dialog and quotes of the novel, and related issues on the topic are taken from printed and online including journal, books, and magazine. In order to achieve the goal of this study the researcher applied theory of character and characterization. Some characteristics that represent Hazel’s and August’s character traits are: depressed, books lover, fighter, stubborn, chivalrous, kind, and loyal. Besides characterization of the main characters this thesis also represents the theme of this novel that is fighting for life.